High variability in physician estimations of flow-diverting stent deployment versus PreSize Neurovascular software simulation: a comparison study - Rai AT; Boo S; Downer J; DuPlessis J; Rautio R; Sinisalo M; Pekkola J; do Nascimento VC; Given C; Patankar T (BMJ PUBLISHING GROUP, 2025)
Background: Physician variablity in preoperative planning of endovascular implant deployment and associated inaccuracies have not been documented. This study aimed to quantify the variability in accuracy of physician flow diverter (FD) planning and directly compares it with PreSize Neurovascular (Oxford Heartbeat Ltd) software simulations.
Methods: Eight experienced neurointerventionalists (NIs), blinded to procedural details, were provided with preoperative 3D rotational angiography (3D-RA) volumetric data along with images annotated with the distal landing location of a deployed Surpass Evolve (Stryker Neurovascular) FD from 51 patient cases. NIs were asked to perform a planning routine reflecting their normal practice and estimate the stent's proximal landing using volumetric data and the labeled dimensions of the FD used. Equivalent deployed length estimation was performed using PreSize software. NI- and software-estimated lengths were compared with postprocedural observed deployed stent length (control) using Bland-Altman plots. NI assessment agreement was assessed with the intraclass correlation coefficient (ICC).
Results: The mean accuracy of NI-estimated deployed FD length was 81% (±15%) versus PreSize's accuracy of 95% (±4%), demonstrating significantly higher accuracy for the software (p<0.001). The mean absolute error between estimated and control lengths was 4 mm (±3.5 mm, range 0.03-30.2 mm) for NIs and 1 mm (±0.9 mm, range 0.01-3.9 mm) for PreSize. No discernable trends in accuracy among NIs or across vasculature and aneurysm morphology (size, vessel diameter, tortuousity) were found.
Conclusions: The study quantified experienced physicians' significant variablity in predicting an FD deployment with current planning approaches. In comparison, PreSize-simulated FD deployment was consistently more accurate and reliable, demonstrating its potential to improve standard of practice.